2015
DOI: 10.1016/j.nicl.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Motor pathway degeneration in young ataxia telangiectasia patients: A diffusion tractography study

Abstract: BackgroundOur understanding of the effect of ataxia–telangiectasia mutated gene mutations on brain structure and function is limited. In this study, white matter motor pathway integrity was investigated in ataxia telangiectasia patients using diffusion MRI and probabilistic tractography.MethodsDiffusion MRI were obtained from 12 patients (age range: 7–22 years, mean: 12 years) and 12 typically developing age matched participants (age range 8–23 years, mean: 13 years). White matter fiber tracking and whole trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 72 publications
5
20
0
Order By: Relevance
“…Additional MRI studies have identified hypomyelinated foci in the cerebrum (Ciemins and Horowitz, 2000), as well as in the cerebellum in A-T patients of different ages (Firat et al, 2005). Indeed, MRI-DTI study on a larger cohort of young patients found that the WM tracts projecting to the cortex, including corticomotor, corticospinal and somatosensory pathways, undergo degeneration (Sahama et al, 2015; Sahama et al, 2014). These clinical findings provide evidence that wide-spread defects in myelination and most likely OL function are part of the A-T phenotype that can be found in additional to the neuronal cell death.…”
Section: Oligodendrocytes and Myelin Are Vulnerable To Genetic Defmentioning
confidence: 99%
“…Additional MRI studies have identified hypomyelinated foci in the cerebrum (Ciemins and Horowitz, 2000), as well as in the cerebellum in A-T patients of different ages (Firat et al, 2005). Indeed, MRI-DTI study on a larger cohort of young patients found that the WM tracts projecting to the cortex, including corticomotor, corticospinal and somatosensory pathways, undergo degeneration (Sahama et al, 2015; Sahama et al, 2014). These clinical findings provide evidence that wide-spread defects in myelination and most likely OL function are part of the A-T phenotype that can be found in additional to the neuronal cell death.…”
Section: Oligodendrocytes and Myelin Are Vulnerable To Genetic Defmentioning
confidence: 99%
“…The nature of axonal 'all-or-nothing' signalling and relationships between activity and subsequent myelination [Demerens et al, 1996;Ishibashi et al, 2006] imply that genuine changes in white matter should occur throughout the entire length of a tract. To confirm that any detected changes reflected genuine change throughout the length of the corticomotor tract, each streamline was binned into seven equal-length sections, using a method previously described [Sahama et al, 2015], and intensities were sampled for each section. An example of this binning is shown in Figure 2.…”
Section: Statistical Analysis Of Tractographymentioning
confidence: 99%
“…In addition to cerebellar atrophy, MRI studies have demonstrated cerebral, white matter abnormalities in older patients, including hemosiderin deposits and deep cerebral telangiectatic vessels, as well as degenerative changes in white matter corticomotor tracts extending from the cerebellum in younger patients with A-T [1719]. …”
Section: Introductionmentioning
confidence: 99%